Stomatal–Hydraulic Coordination Mechanisms of Wheat in Response to Atmospheric–Soil Drought and Rewatering - Lijuan Wang; Yanqun Zhang; Hao Li; Xinlong Hu; Pancen Feng; Yan Mo; Shihong Gong (Agriculture)
Drought stress severely limits agricultural productivity, with atmospheric and soil water deficits often occurring simultaneously in field conditions. While plant responses to individual drought factors are well-documented, recovery mechanisms following combined atmospheric–soil drought remain poorly understood, hindering drought resistance strategies and irrigation optimization. We set up two VPD treatments (low and high vapor pressure deficit) and two soil moisture treatments (CK: control soil moisture with sufficient irrigation, 85–95% field capacity; drought: soil moisture with deficit irrigation, 50–60% field capacity) in the pot experiment. We investigated wheat’s hydraulic transport (leaf hydraulic conductance, Kleaf) and gas exchange (stomatal conductance, gs; photosynthetic rate, An) responses to combined drought stress from atmospheric and soil conditions at the heading stage, as well as rewatering 55 days after treatment initiation. The results revealed that: (1) high VPD and soil drought significantly reduced leaf hydraulic conductance (Kleaf), with a high VPD decreasing Kleaf by 31.6% and soil drought reducing Kleaf by 33.2%; The high VPD decreased stomatal conductance (gs) by 43.6% but the photosynthetic rate (An) by only 12.3%; (2) After rewatering, gs and An of atmospheric and soil drought recovered relatively rapidly, while Kleaf did not; (3) Atmospheric and soil drought stress led to adaptive changes in wheat’s stomatal regulation strategies, with an increasing severity of drought stress characterized by a shift from non-conservative to conservative water regulation behavior. These findings elucidate wheat’s hydraulic–stomatal coordination mechanisms under drought stress and their differential recovery patterns, providing theoretical foundation for improved irrigation management practices.